Pengembangan Modul Ajar Digital Kalimat Efektif Berbantuan Aplikasi Kotobee bagi Mahasiswa - Amanah, Amanah; Cahyani, Putri Ayu; Awaliyah, Mia (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Constructing effective sentences is a crucial skill that university students must possess as future academics. This skill significantly influences the effectiveness of both oral and written communication. The purpose of this research is to produce a digital teaching module on effective sentence construction, supported by the Kotobee application, for university students. This study is a research and development (R&D) project employing the ADDIE model, which includes the stages of Analyze, Design, Development, Implementation, and Evaluation. Research data were obtained through observations and questionnaires involving experts in language, subject matter, and digital module design. The instruments used for data collection were observation sheets and questionnaires. The data were analyzed using descriptive quantitative techniques based on the scores provided by validators and users. The design aspect of the module was evaluated on several components: (1) visual appeal received 54% 'very appropriate' and 37% 'appropriate'; (2) readability received 70% 'very appropriate' and 25% 'appropriate'; (3) layout received 62% 'very appropriate' and 33% 'appropriate'; and (4) image quality received 63% 'very appropriate'. Meanwhile, the content aspect was assessed through: (1) completeness and clarity of material, with 66.7% rated as 'very appropriate'; (2) presentation of examples, 59.8% 'very appropriate'; and (3) provision of practice questions, 56% 'very appropriate'. Based on these findings, it can be concluded that the digital teaching module on effective sentence construction meets the feasibility criteria in terms of both design and content